The Effect of Part‐Time Work on Wages: Evidence from the Social Security Rules - Aaronson, Daniel; French, Eric (Journal of Labor Economics, 2004)
This article identifies the part‐time wage effect, using hours variation caused by the social security rules. We show that work hours and wages drop sharply at ages 62 and 65. We argue that the hours decline causes the wage decline, resulting in a 25% wage penalty for men who cut their work week from 40 to 20 hours. However, we find little evidence for such an effect among women. We also show that models that fail to account for the joint determination of hours and wages will understate the labor supply response to a tax change by about 26%.